Microbially mediated mechanisms underlie soil carbon accrual by conservation agriculture under decade-long warming - Tian, Jing; Dungait, Jennifer A. J.; Hou, Ruixing; Deng, Ye; Hartley, Iain P.; Yang, Yunfeng; Kuzyakov, Yakov; Zhang, Fusuo; Cotrufo, M. Francesca; Zhou, Jizhong (Nature communications, 2024)
Increasing soil organic carbon (SOC) in croplands by switching from conventional to conservation management may be hampered by stimulated microbial decomposition under warming. Here, we test the interactive effects of agricultural management and warming on SOC persistence and underlying microbial mechanisms in a decade-long controlled experiment on a wheat-maize cropping system. Warming increased SOC content and accelerated fungal community temporal turnover under conservation agriculture (no tillage, chopped crop residue), but not under conventional agriculture (annual tillage, crop residue removed). Microbial carbon use efficiency (CUE) and growth increased linearly over time, with stronger positive warming effects after 5 years under conservation agriculture. According to structural equation models, these increases arose from greater carbon inputs from the crops, which indirectly controlled microbial CUE via changes in fungal communities. As a result, fungal necromass increased from 28 to 53%, emerging as the strongest predictor of SOC content. Collectively, our results demonstrate how management and climatic factors can interact to alter microbial community composition, physiology and functions and, in turn, SOC formation and accrual in croplands. Agricultural soil C dynamics under climate change are difficult to predict. Here, the authors report that experimental warming increases soil organic C stocks in conservation agriculture but not in conventional agriculture, which appears driven by soil microbial responses to no tillage and C inputs from the crops.